Dynamic complementarity in skill production: Evidence from genetic endowments and birth order - Dilnoza Muslimova; Hans van Kippersluis; Cornelius A. Rietveld; Stephanie von Hinke; S. Fleur W. Meddens (Tinbergen Institute, 2020)
The birth order literature emphasizes the role of parental investments in explaining why firstborns have higher human capital outcomes than their laterborn siblings. We use birth order as a proxy for investments and interact it with genetic endowments. Exploiting only within-family variation in both ensures they are exogenous as well as orthogonal to each other. As such, our setting is informative about the existence of dynamic complementarity in skill production. Our empirical analysis exploits data from 15,019 full siblings in the UK Biobank. We adopt a family-fixed effects strategy combined with instrumental variables to deal with endogeneity issues arising from omitted variables and measurement error. We find that birth order and genetic endowments interact: those with above-average genetic endowments benefit disproportionally more from being firstborn compared to those with below-average genetic endowments. This finding is a clean example of how genetic endowments ('nature') and the environment ('nurture') interact in producing educational attainment. Moreover, our results are consistent with the existence of dynamic complementarity in skill formation: additional parental investments associated with being firstborn are more `effective' for those siblings who randomly inherited higher genetic endowments for educational attainment.
Keywords: D15; I24; J24; 330; Birth order; dynamic complementarity; gene-environment interaction; educational attainment; polygenic score